MMP modulated differentiation of mouse embryonic stem cells on engineered cell derived matrices. (January 2022) - Sthanam, Lakshmi Kavitha; Roy, Tanusri; Patwardhan, Sejal; Shukla, Avi; Sharma, Shipra; Shinde, Pradip V.; Kale, Hanuman Tulasiram; Chandra Shekar, P.; Kondabagil, Kiran; Sen, Shamik
Abstract: Stem cell differentiation is dictated by the dynamic crosstalk between cells and their underlying extracellular matrix. While the importance of matrix degradation mediated by enzymes such as matrix metalloproteinases (MMPs) in the context of cancer invasion is well established, the role of MMPs in stem cell differentiation remains relatively unexplored. Here we address this question by assaying MMP expression and activity during differentiation of mouse embryonic stem cells (mESCs) on mouse embryonic fibroblast (MEF) derived matrices (MEFDMs) of varying stiffness and composition. We show that mESC differentiation into different germ layers is associated with expression of several MMPs including MMP-11, 2, 17, 25 and 9, with MMP-9 detected in cell secreted media. Different extents of softening of the different MEFDMs led to altered integrin expression, activated distinct mechanotransduction and metabolic pathways, and induced expression of germ layer-specific markers. Inhibition of MMP proteolytic activity by the broad spectrum MMP inhibitor GM6001 led to alterations in germ layer commitment of the differentiating mESCs. Together, our results illustrate the effect of MMPs in regulating mESC differentiation on engineered cell derived matrices and establish MEFDMs as suitable substrates for understanding molecular mechanisms regulating stem cell development and for regenerative medicine applications.